Hanna Tadeusiewicz – the Scientist and the Teacher (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The article presents the scientific profile of Professor Hanna Tadeusiewicz. The authors focused on presenting the areas of scientific interest of the researcher, her didactic activity and the most important publications published in 2010–2017. The various periods of the Professor’s academic activity were described with particular emphasis on the doctoral dissertation exam in April 1970. The following methods were used to implement the topic: critical analysis of the literature, historical and bibliographical methods.